Review of Fiqh Legal and Positive Law Regarding Divorce Procedure - Lilis Handayani (International Journal of Integrative Research, 2023)
This research explains the review of fiqh legal and positive law regarding the procedures for divorce. the purpose of writing this article is to provide education, information and advocacy to readers so that divorce is carried out in a civilized manner by adhering to fiqh legal procedures and positive law. this type of research is qualitative legal research and normative legal research, namely what we know as library law research, namely legal articles that are carried out by researching based on materials sourced from the literature. the data sources used by the author in this article include primary legal materials, namely applicable laws and regulations which provide a description of primary legal materials in the form of commentaries, general books, journals, documents and other references related to this article. the results of writing this article are: first, the husband has the authority to give talaq or divorce his wife if the problem at hand has no way of solving the problem. second, husband and wife should always prioritize peaceful mediation and avoid conflicts that can trigger household damage. third, divorce should follow the legal mechanism of fiqh and positive law according to existing regulations.